2019
DOI: 10.1017/s0305000919000060
|View full text |Cite
|
Sign up to set email alerts
|

The development of vocabulary and grammar: a longitudinal study of European Portuguese-speaking toddlers

Abstract: The goals of this study were to analyze the growth and stability of vocabulary, mean length of the three longest utterances (MLLUw), and sentence complexity in European Portuguese-speaking children aged 1;4–2;6, to explore differences in growth as a function of personal and family-related variables, and to investigate the inter-relationships among the three language dimensions. Fifty-one European Portuguese-speaking toddlers were longitudinally assessed at 1;4, 1;9, 2;1, and 2;6, through parent reports. Expone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
0
7
1
Order By: Relevance
“…The only other study to explore the relationship between vocabulary and grammar considering not only trait‐like stability, but also the relationship between this and the growth of the constructs (Hoff et al., 2018) was conducted with younger bilingual children, up to the age of 4, and found no relationship between intercepts and amount of growth, either within or between constructs when these were assessed in English. The difference between Hoff et al.’s (2018) results and those of the present study is not entirely surprising as the relationship between vocabulary and grammar seems to change over time, with longitudinal studies with children younger than 3 usually showing either a bidirectional relationship or a primacy for vocabulary (Cadime et al., 2019; Dionne et al., 2003; Marjanovic‐Umek et al., 2017). It is possible that this change might be linked to exposure rather than age, which would suggest that bilingual children might show the directional switch later as a function of reduced relative amount of input.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…The only other study to explore the relationship between vocabulary and grammar considering not only trait‐like stability, but also the relationship between this and the growth of the constructs (Hoff et al., 2018) was conducted with younger bilingual children, up to the age of 4, and found no relationship between intercepts and amount of growth, either within or between constructs when these were assessed in English. The difference between Hoff et al.’s (2018) results and those of the present study is not entirely surprising as the relationship between vocabulary and grammar seems to change over time, with longitudinal studies with children younger than 3 usually showing either a bidirectional relationship or a primacy for vocabulary (Cadime et al., 2019; Dionne et al., 2003; Marjanovic‐Umek et al., 2017). It is possible that this change might be linked to exposure rather than age, which would suggest that bilingual children might show the directional switch later as a function of reduced relative amount of input.…”
Section: Discussioncontrasting
confidence: 84%
“…Using cross-lagged panel models, Caglar-Ryeng et al (2019) explored the relationship between measures of vocabulary and grammar in children with a family risk of dyslexia and a control group between the ages of 1 and 6 months and 6 and 0 and reported bidirectional crosslagged effects before the age of 3 years, but only cross-lagged effects of grammar over vocabulary after 3 and 6. In a study of children between 1 and 4 and 2 and 6, Cadime et al (2019) reported a unidirectional significant relationship between vocabulary and MLU at 1 and 9 and sentence complexity at 2 and 1, with a stronger effect of vocabulary on these two measures of grammar. The only significant relationship with vocabulary at 2 and 1 was vocabulary at 1 and 9.…”
Section: Modeling Evidence For Directionality In the Relationship Between Vocabulary And Grammarmentioning
confidence: 97%
See 2 more Smart Citations
“…Most often studied among pre-verbal infants, CDS is characterized by unusual auditory features such as high pitch, slow pace, exaggerated prosody, and distinct timbre; as well as sparse word volume and frequent repetition of words, focus on concrete ideas, and simple syntactic structure ( Rowe, 2008 , 2012 ; Huttenlocher et al, 2010 ; Longobardi et al, 2016 ; Quick et al, 2019 ; Genovese et al, 2020 ; Rowe and Snow, 2020 ). Adults’ CDS changes as children progress into toddlerhood (e.g., 1–2 years of age) and begin to talk and respond on their own ( Durán et al, 2004 ; Hoff, 2014 ) using one-, two-, or three-word phrases (i.e., telegraphic speech) ( Rice et al, 2010 ) undergirded by basic syntax and grammar ( Hoff et al, 2018 ; Cadime et al, 2019 ). Adults’ CDS to toddlers employs more standard prosody and longer utterances, with more numerous and complex words and grammatical structures, as well as increased back-and forth through extended adult-child conversations fostered by questions ( Rowe, 2012 ; Longobardi et al, 2016 ).…”
Section: Child-directed Speechmentioning
confidence: 99%